2021
DOI: 10.1186/s12870-020-02764-y
|View full text |Cite
|
Sign up to set email alerts
|

The NAC-type transcription factor CaNAC46 regulates the salt and drought tolerance of transgenic Arabidopsis thaliana

Abstract: Background The NAC (NAM, ATAF1/ATAF2, and CUC2) transcription factors belong to a large family of plant-specific transcription factors in monocot and dicot species. These transcription factors regulate the expression of stress tolerance-related genes that protect plants from various abiotic stresses, including drought, salinity, and low temperatures. Results In this study, we identified the CaNAC46 transcription factor gene in Capsicum annuum. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…The AtRD29B is one of the key stress response genes always analyzed in gene function analysis. Its up-regulated expression is usually associated with the tolerance of transgenic plants to salt or other abiotic stresses [ 35 , 51 , 52 ]. In this study, we found that AtRD29B was significantly upregulated by overexpression MeAnn2 gene in Arabidopsis under salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The AtRD29B is one of the key stress response genes always analyzed in gene function analysis. Its up-regulated expression is usually associated with the tolerance of transgenic plants to salt or other abiotic stresses [ 35 , 51 , 52 ]. In this study, we found that AtRD29B was significantly upregulated by overexpression MeAnn2 gene in Arabidopsis under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress affects the lateral root number, root development, and root growth direction of plants by regulating the concentration gradient and redistribution of IAA [ 53 ]. The previous research indicated that the high expression of AtLBD18 and AtIAA4 was related to the salt tolerance of transgenic Arabidopsis [ 35 ]. In our analysis of transgenic Arabidopsis overexpressing MeAnn2 under salt stress, in which salt tolerance was enhanced compared to WT, it was found that the expression levels of the related genes AtIAA4 and AtLBD18 in the auxin signaling pathway were significantly increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations